Attitudes toward women managers in public sector of Pakistan and its impact on their career progression & Quality of life Moderating role of Masculinity/Feminity - sarwar, salman (Journal of Contemporary Research in Management (JCRM), 2017)
This paper examines attitudes toward woman managers more specifically; this paper tries to identify the impact of attitude and different stereotypes on woman career progression and quality of life with moderating role of Masculinity/Feminity. To address the purpose, data was collected from 80 Female managers from Public sector organizations. Then data was analyzed by using correlation and regression analysis. The analysis indicates that; there was significant positive relationship between Attitude towards women manager and masculinity/Feminity. Second Masculinity/Femininity moderates the relationship between ATWM and career progression in such a way that high Masculinity/Femininity will weaken the relationship. Implication of results and limitations are also discussed in the paper.